Advantage of Minimally Invasive Lateral Approach Relative to Conventional Deltopectoral Approach for Treatment of Proximal Humerus Fractures - Liu, Kuan (Med Sci Monit, 2015)
BACKGROUND: Despite the wide application of open reduction and internal fixation with locking plates for the treatment of proximal humeral fractures, the surgical invasive approach remains controversial. This study aimed to evaluate the pros and cons of the minimally invasive lateral approach for the treatment of proximal humeral fracture (PHF) in comparison with the deltopectoral approach. MATERIAL/METHODS: All patients who sustained a PHF and received open reduction and internal fixation (ORIF) surgery with locking plate through either minimally invasive subacromial approach or conventional deltopectoral approach between January 2008 and February 2012 were retrospectively analyzed. Patients were divided into the conventional group and min-group according to the surgical incision. Surgery-related information, postoperative radiography, complications, and shoulder functional measurement scores in a 2-year follow-up were collected and evaluated. RESULTS: Ninety-one patients meeting the inclusion criteria were included in this study. We observed a significant difference in both surgery time (81.8±18.3 vs. 91.0±18.4) (p=0.021) and blood loss (172±54.2 vs. 205±73.6) (p=0.016) between the min-group and conventional group. Compared to the conventional group, the min-group had significantly better Constant-Murley score and DASH score at early follow-up (p<0.05) and higher patients satisfaction rate (8.1±1.1 vs. 7.6±1.2) (p= 0.019). The multiple linear regression analysis indicated that age, PHF types, surgical groups, surgery time, and blood loss have significant effect on the activity of affected shoulder in both abduction and forward flexion (p<0.05) except for gender factor. While larger range of movement of the affected shoulder, mainly in the 2-part and 3-part fractures, was observed in the min-group, the conventional group obtained better movement in the 4-part fractures. CONCLUSIONS: The minimally invasive lateral approach is the optimal alternative for the treatment of Neer’s type 2 and 3 proximal humerus fractures.